Предмет: Алгебра,
автор: Solnce58
помогите, прошу, даю 30 баллов!
Приложения:
![](https://files.topotvet.com/i/1ad/1ad2974c77e01bddf2819a50a245b851.jpg)
Ответы
Автор ответа:
1
Ответ: x=7.
Объяснение:
1+√(1+x*√(x²-24))=x
√(1+x*√(x²-24))=x-1
ОДЗ:
{x-1≥0 {x≥1 x∈[1;+∞)
{x²-24≥0 {x²≥24 x²-24≥0 (x-√24)(x+√24)≥0
x∈(-∞;-2√26]U[2√6;+∞) ⇒ x∈[2√6;+∞).
(√(1+x*√(x²-24)))²=(x-1)²
1+x*√(x²+24)=x²-2x+1
x*√(x²-24)=x²-2x
x*√(x²-24)-x²+2x=0
x*(√(x²-24)-x+2)=0
x=0 ∉ОДЗ
√(x²-24)-x+2=0
√(x²-24)=x-2
(√(x²-24))²=(x-2)²
x²-24=x²-4x+4
4x=28 |÷4
x=7 ∈ ОДЗ.
Похожие вопросы
Предмет: Право,
автор: zubkoa369
Предмет: Алгебра,
автор: radmirf07
Предмет: Русский язык,
автор: LIRIKOT
Предмет: Физика,
автор: гепардёнок
Предмет: История,
автор: sSiMmoNn